Correction for the taxonomy of Trichomanes foeniculaceum as synonym of Abrodictyum parviflorum (Hymenophyllaceae, Polypodiidae) - Dubuisson, Jean-Yves; Hennequin, Sabine (Phytotaxa, 2018)
In Dubuisson et al. (2017), Trichomanes foeniculaceum (Hooker 1845: 135) is cited as a heterotypic synonym of Abrodictyum parviflorum (Poiret 1808: 83) Bauret & Dubuisson (2017: 211), which was newly combined and proposed as the valid name of Abrodictyum meifolium (Bory ex Willdenow 1810: 509, 510) Ebihara & Dubuisson (2006: 144), a widespread species in the western Indian Ocean. The proposed authorship for T. foeniculaceum in Dubuisson et al. (2017) (i.e., Hooker 1845: 135) was in accordance with the Tropicos database (www.tropicos.org; as consulted in 2017) and Roux (2009). However, the valid author is actually Bory ex Willdenow (1810: 511), as also reported in IPNI (www.ipni.org) and by Tardieu-Blot (2008). We propose thus hereafter the corrected taxonomy for A. parviflorum including T. foeniculaceum as a synonym.